Come together: calibration of tiger shark (Galeocerdo cuvier) microsatellite databases for investigating global population structure and assignment of historical specimens - M. Sort; A. Manuzzi; B. Jiménez-Mena; J. R. Ovenden; B. J. Holmes; A. M. Bernard; M. S. Shivji; D. Meldrup; M. B. Bennett; E. E. Nielsen (Conservation Genetics Resources, 2021)

Microevolution in time and space: SNP analysis of historical DNA reveals dynamic signatures of selection in A tlantic cod - Nina O. Therkildsen; Jakob Hemmer‐Hansen; Thomas D. Als; Douglas P. Swain; M. Joanne Morgan; Edward A. Trippel; Stephen R. Palumbi; Dorte Meldrup; Einar E. Nielsen (Molecular Ecology, 2013)
Little is known about how quickly natural populations adapt to changes in their environment and how temporal and spatial variation in selection pressures interact to shape patterns of genetic diversity. We here address these issues with a series of genome scans in four overfished populations of Atlantic cod ( G adus morhua ) studied over an 80‐year period. Screening of >1000 gene‐associated single‐nucleotide polymorphisms ( SNP s) identified 77 loci that showed highly elevated levels of differentiation, likely as an effect of directional selection, in either time, space or both. Exploratory analysis suggested that temporal allele frequency shifts at certain loci may correlate with local temperature variation and with life history changes suggested to be fisheries induced. Interestingly, however, largely nonoverlapping sets of loci were temporal outliers in the different populations and outliers from the 1928 to 1960 period showed almost complete stability during later decades. The contrasting microevolutionary trajectories among populations resulted in sequential shifts in spatial outliers, with no locus maintaining elevated spatial differentiation throughout the study period. Simulations of migration coupled with observations of temporally stable spatial structure at neutral loci suggest that population replacement or gene flow alone could not explain all the observed allele frequency variation. Thus, the genetic changes are likely to at least partly be driven by highly dynamic temporally and spatially varying selection. These findings have important implications for our understanding of local adaptation and evolutionary potential in high gene flow organisms and underscore the need to carefully consider all dimensions of biocomplexity for evolutionarily sustainable management.

Microsatellite standardization and evaluation of genotyping error in a large multi-partner research programme for conservation of Atlantic salmon (Salmo salar L.) - J. S. Ellis; J. Gilbey; A. Armstrong; T. Balstad; E. Cauwelier; C. Cherbonnel; S. Consuegra; J. Coughlan; T. F. Cross; W. Crozier; E. Dillane; D. Ensing; et al. (Genetica, 2011)

Distribution of individual inbreeding coefficients, relatedness and influence of stocking on native anadromous brown trout ( Salmo trutta ) population structure - D. E. Ruzzante; M. M. Hansen; D. Meldrup (Molecular Ecology, 2001)
We examined polymorphism at seven microsatellite loci in 4023 brown trout ( Salmo trutta ) collected from 32 tributaries to the Limfjord, Denmark (~200 km) and from two hatcheries used for stocking. Populations differ in their estimated sizes and stocking histories. Mean individual inbreeding coefficients do not differ among locations within rivers. Relatedness varies between sites within rivers indicating varied local dynamics at a very small geographical scale. Relatedness is sometimes lower than expected among an equal number of simulated individuals with randomized genotypes, suggesting structure within locations. Five per cent of the genetic variance is distributed among rivers ( F ST = 0.049), but in the western, less heavily stocked, area of the Limfjord a higher proportion of the genetic variance is distributed among rivers than among locations within rivers. The reverse is true of the eastern, more heavily stocked, area of the Limfjord. Here, a higher proportion of the genetic variance is distributed among locations within rivers than among rivers. Assignment tests reveal that the majority of trout (mean 77% of all fish) are more probably of local origin than hatchery origin but this proportion varies regionally, with rivers in the western area of the Limfjord showing a relatively high (mean 88%) and those in the eastern area showing a relatively low (mean 72%) proportion of locally assigned trout. These results can be interpreted as reflecting stocking impact. Also, the proportion of locally assigned trout correlates with the populations’ stocking histories, with rivers presently subjected to stocking (hatchery trout) showing low (mean ~0.73), and rivers where stocking was discontinued showing high (mean ~0.84) proportions of local fish, probably reflecting lower survival of hatchery than of wild trout. There is evidence for isolation by distance at a large geographical scale when individual river populations are pooled into nine geographical regions but not at a small geographical scale when populations are considered individually. We reject the null hypothesis that stocking has had no impact on population structure but the relatively high proportion of locally assigned trout in populations where stocking with domestic fish no longer takes place suggests limited long‐term success of stocking.

Development of new VNTR markers for pike and assessment of variability at di‐ and tetranucleotide repeat microsatellite loci - M. M. Hansen; J. B. Taggart; D. Meldrup (Journal of Fish Biology, 1999)
Levels of variation at six VNTR (variable number of tandem repeats) loci, one minisatellite and five microsatellite loci, isolated from tri‐ and tetranucleotide enriched DNA libraries for northern pike were generally low in two Danish populations (1–4 alleles; expected heterozygosity 0–0·57), though one highly variable microsatellite (13 alleles; expected heterozygosity 0·79) was identified. In combination with previously published microsatellites a set consisting of nine polymorphic loci appeared to be useful for discriminating populations, as determined by assignment tests.